2020
DOI: 10.1016/j.jhin.2020.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba castellanii interferes with adequate chlorine disinfection of multidrug-resistant Pseudomonas aeruginosa

Abstract: Verona-Integron-encoded-Metallo-b-lactamase-positive Pseudomonas aeruginosa (VIM-PA) is a cause of hard-to-treat nosocomial infections, and can colonize hospital water networks alongside Acanthamoeba. We developed an in-vitro disinfection model to examine whether Acanthamoeba castellanii can harbour VIM-PA intracellularly, allowing VIM-PA to evade being killed by currently used hospital disinfectants. We observed that A. castellanii presence resulted in significantly increased survival of VIM-PA after exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Interestingly, PA B80425 did not remain at elevated levels on day 7 and instead showed another reduction in growth compared to mono-culture suggesting that it is less robust than the other strains when in the presence of amoebae. The environmental isolates all survived at a greater concentrations in co-culture than in mono-culture over all 4 time points suggesting that these particular strains, at least, were well-prepared for co-culture with amoebae which is not surprising as both P. aeruginosa and A. castellanii are likely to share environmental niches and A. castellanii has been shown to aid in the extracellular survival of other bacterial species [49, 50]. Raw survival counts for P. aeruginosa are provided in S1 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PA B80425 did not remain at elevated levels on day 7 and instead showed another reduction in growth compared to mono-culture suggesting that it is less robust than the other strains when in the presence of amoebae. The environmental isolates all survived at a greater concentrations in co-culture than in mono-culture over all 4 time points suggesting that these particular strains, at least, were well-prepared for co-culture with amoebae which is not surprising as both P. aeruginosa and A. castellanii are likely to share environmental niches and A. castellanii has been shown to aid in the extracellular survival of other bacterial species [49, 50]. Raw survival counts for P. aeruginosa are provided in S1 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa and A. castellanii are likely to share environmental niches and A. castellanii has been shown to aid in the extracellular survival of other bacterial species [49,50]. Raw survival counts for P. aeruginosa are provided in S1 Fig.…”
Section: Impact Of P Aeruginosa Strain On a Castellanii Survivalmentioning
confidence: 99%
“…We used the in-vitro disinfection protocol with chlorine (hypochlorous acid) as described earlier [10] to investigate whether, in the presence of V. vermiformis, M. chimaera is protected against disinfectant. This procedure was necessary because the Puristeril340, used for disinfection of the HCUs, cannot be neutralized effectively, which is necessary to investigate the survival of M. chimaera.…”
Section: Disinfectionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is an opportunistic pathogen that is commonly found in a wide range of environmental habitats, including soil, water, plants, and animals ( 10 ). P. aeruginosa has been demonstrated to be associated with a range of infections, including urinary tract infections, pneumonia, wound infections, and sepsis ( 11 ). Corneal infection is one of the prominent clinical manifestations associated with P. aeruginosa infections and is often attributed to factors such as contact lens use or eye injury ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A. castellanii and P. aeruginosa are widespread pathogenic microorganisms that cause certain human diseases ( 18 , 19 ). Experimental evidence suggests that A. castellanii can interfere with the efficacy of hospital disinfection with chlorine, which leads to increased bacterial survival ( 11 ). Animal studies have indicated that bacterial presence participates in the development of AK ( 20 ).…”
Section: Introductionmentioning
confidence: 99%